Perancangan Tata Letak Alat Pemadam Api Ringan pada Proyek Rumah Sakit - Abrar Sajidan Firzatullah; Ida Umarul Mufidah; Nico Linggi Pongmasangka (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Fire incidents in Indonesia remain relatively high, with a total of 2,286 cases recorded. In 2022, the frequency of fires in Jakarta reached 1,691 cases, marking a 10% increase compared to the previous year, which had successfully reduced fire frequency by 23%. The high fire risk in high-rise buildings can lead to both material losses and casualties. This study aims to design the layout and determine the requirements for portable fire extinguishers  in a hospital project in Jakarta. The design of the fire extinguisher layout and requirements is intended for the operational phase of the building, ensuring optimal applicability. The location, area, and/or environment with various work activities and risk levels ranging from low to high indicate that safety is of paramount importance and must be prioritized, and that any form of accident should be addressed as early as possible. This research employed a qualitative descriptive method to describe and illustrate existing phenomena, both natural and human-engineered, through observation, interviews, and documentation. The findings show that the design of the fire extinguisher layout and requirements amounted to 61 units across the 4th to 7th floors, with the fire extinguisher layout plan attached. The type of fire extinguisher used on each floor is a 6-kg dry powder extinguisher. The conducted fire risk assessment indicates that each floor presents a moderate hazard, while some rooms exhibit a high hazard level. This study provides recommendations for the placement and requirements of fire extinguisher in accordance with standards and is expected to contribute to fire prevention efforts in the hospital project in Jakarta once it becomes operational.